2013
DOI: 10.1645/12-33.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Detection ofCryptosporidiumandIsospora(Cystoisospora) Oocysts According to the Fecal Concentration or Staining Method Used in a Clinical Laboratory

Abstract: Despite the availability of many parasitological methods for detection of Cryptosporidium and Isospora (Cystoisospora) belli in fecal samples, there are uncertainties about the accuracy of these techniques in laboratory practice. In this study, 27 formalin-fixed positive stool samples for Cryptosporidium and 15 for I. belli were analyzed by 2 concentration methods, sedimentation by centrifugation (SC) and formalin-ethyl acetate (FE), and by 3 tintorial techniques, modified Ziehl-Neelsen (ZN), safranin (SF), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…The effectiveness of this technique is that it produces a much cleaner product, due in large part to the ethyl acetate extraction of fats, which is of particular importance for immunofluorescence assay (IFA) staining of Cryptosporidium to reduce the level of background fluorescence. There may also be validity to the move to perform a modified concentration technique without using formalin (88,89). Perhaps by removing formalin, subtle changes in the specific gravity of the suspending solution may be sufficient to ensure recovery of oocysts of very low density.…”
Section: Methods For the Detection Of Cyclospora Cystoisospora Crypmentioning
confidence: 99%
“…The effectiveness of this technique is that it produces a much cleaner product, due in large part to the ethyl acetate extraction of fats, which is of particular importance for immunofluorescence assay (IFA) staining of Cryptosporidium to reduce the level of background fluorescence. There may also be validity to the move to perform a modified concentration technique without using formalin (88,89). Perhaps by removing formalin, subtle changes in the specific gravity of the suspending solution may be sufficient to ensure recovery of oocysts of very low density.…”
Section: Methods For the Detection Of Cyclospora Cystoisospora Crypmentioning
confidence: 99%
“…diagnosis. In a previous report, we showed that the concentration of oocysts by CS, followed by mZn staining, proved to be a suitable protocol for Cryptosporidium detection in human faeces (7). Moreover, the ZS method showed lower sensitivity and specificity compared to saturated sugar solution flotation technique for Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 96%
“…Spontaneous sedimentation, centrifugal sedimentation, or formalin-ethyl acetate are widely used for the diagnosis of intestinal protozoa and helminths in human and animal stool samples (5)(6)(7)(8). The faecal concentration methods based on sedimentation of parasites are useful for recovering heavy parasite eggs due to the concentration of the organisms in the sediment, whereas the centrifugal-flotation in zinc sulphate (9) is used preferentially to recover protozoa cysts because of the low density of parasitic forms as compared to the salt solution.…”
mentioning
confidence: 99%
“…Stool samples were subjected to the following parasitological tests: (a) sedimentation by centrifugation in water [19]; (b) zinc sulfate (density of solution 1.18 g/mL) centrifugal flotation [20]; and (c) modified Ziehl-Neelsen staining [21]. Two slides were examined for each test.…”
Section: Diagnosis Of Intestinal Parasites In Fecal Samplesmentioning
confidence: 99%